MANAGEMENT-BASED CLUSTERING IN FISHERY AGROINDUSTRIES PRODUCTS: A CASE STUDY OF JEMBER REGENCY - Hadi Paramu (Journal of Economics, Business, and Accountancy Ventura, 2011)
Recently, the classical problems dealing with raw materials (fish) supply, technology avail- ability, and business management remain to happen in fishery products. In facing such prob- lems, an integrated and comprehensive solution should strongly be implemented. This study aims to study managerial characteristics of agro industries in coastal areas of Jember re- gency using managerial clustering method. The population of the study was all fishery agro industry business units of the selected areas. The respondents were determined by snowball sampling method in every coastal area, consisting of 79 businessmen in the agro industry. They were interviewed concerning the aspects in the study, and cluster analysis method was conducted. It reveals that, based on managerial characteristics, there were two clusters of fishery agro industry identified, namely (1) cluster of fishery agro industry using a conven- tional management practices and (2) that of fishery agro industry using a formal/modern management. The first cluster comprises a dominant one because 68 businesses were in this cluster while the second one comprises 11 businesses applying a formal or modern manage- ment practice. One of the implications relevant to this result is that all efforts to resolve the problems of fishery agro industries should be based on managerial characteristics in each of the clusters